Implementasi Python Folium dalam Pembangunan Sistem Informasi Peta Interaktif Cagar Budaya Provinsi Bali - Subiksa, Gde Brahupadhya; Ariawan, Made Pasek Agus; Peling, Ida Bagus Adisimakrisna (MEANS (Media Informasi Analisa dan Sistem), 2023)
The journal titled "Implementation of Python and Folium in Developing an Interactive Cultural Heritage Map Website for Bali Province" explores the effective utilization of Python and Folium in developing an interactive map website that showcases Bali Province's cultural heritage sites. The study focuses on creating a visually appealing and user-friendly platform to promote the exploration and preservation of Bali's cultural treasures. Python and Folium were employed to develop dynamic maps that allow users to navigate and interact with the cultural sites seamlessly. The website's implementation was evaluated using the WebQual 4.0 framework, which assesses dimensions such as usability, information quality, service quality, and user satisfaction. The research findings revealed an impressive overall score of 82.6% on the WebQual 4.0 evaluation, indicating high-quality implementation and user satisfaction. The integration of Python and Folium enabled a captivating and immersive experience, providing comprehensive information about the cultural sites and facilitating smooth navigation. By leveraging Python and Folium, the developed website serves as a valuable educational resource and promotes cultural awareness. It encourages tourism and appreciation for Bali's unique cultural heritage by offering an engaging platform for users to explore the diverse cultural sites.In conclusion, the study highlights the successful implementation of Python and Folium in developing an interactive map website for Bali's cultural heritage. With its visually appealing design and user-friendly interface, the website provides an accessible means for individuals to discover and appreciate Bali's rich cultural treasures.